2022
DOI: 10.3389/fgene.2022.880387
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism-Related lncRNA Signature Predicts the Prognosis of Breast Cancer

Abstract: Background and Purpose: Breast cancer (BRCA) is the most frequent female malignancy and is potentially life threatening. The amino acid metabolism (AAM) has been shown to be strongly associated with the development and progression of human malignancies. In turn, long noncoding RNAs (lncRNAs) exert an important influence on the regulation of metabolism. Therefore, we attempted to build an AAM-related lncRNA prognostic model for BRCA and illustrate its immune characteristics and molecular mechanism.Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Previous studies have found that lncRNA LIPE-AS1 is overexpressed in a variety of tumor types, including cervical cancer and breast cancer, compared with normal tissues. Several studies have also shown that high expression of LIPE-AS1 is associated with better prognosis ( Liu et al, 2021a ; Xu et al, 2021 ; Dai et al, 2022 ), consistent with our results. Xu et al showed that the expression of LIPE-AS1 was significantly correlated with that of the PD-L1 gene ( Xu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found that lncRNA LIPE-AS1 is overexpressed in a variety of tumor types, including cervical cancer and breast cancer, compared with normal tissues. Several studies have also shown that high expression of LIPE-AS1 is associated with better prognosis ( Liu et al, 2021a ; Xu et al, 2021 ; Dai et al, 2022 ), consistent with our results. Xu et al showed that the expression of LIPE-AS1 was significantly correlated with that of the PD-L1 gene ( Xu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also listed the other signatures that focus more on short-term (3- and 5-year survival) survival. We found our signature usually have better short-term survival prognostic value compared with them, such as the necroptosis-related lncRNA signature ( Zhang et al, 2022 ), hypoxia-related lncRNA signature ( Zhao et al, 2021 ), autophagy-related lncRNA signature ( Li et al, 2021 ), ferroptosis-related lncRNA signature ( Jia et al, 2021 ), N6-methyladenosine-related lncRNA signature ( Lv et al, 2021 ), acid metabolism-related lncRNA signature ( Dai et al, 2022 ), and CD4 + conventional T cells-related lncRNA signature ( Ning et al, 2022 ) and pyroptosis-related lncRNA signature ( Yang et al, 2021 ). In addition, our model only involves 7 lncRNAs, while other models (6/11) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 96%
“…In this study, we have found that USP30-AS1 influences the activation of macrophage-like cells. Interestingly, USP30-AS1 has been implicated to be a potential prognostic risk factor for cancer and to play a role in cell death (e.g., apoptosis, autophagy, ferroptosis, and necroptosis) [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Furthermore, USP30-AS1 promotes cell viability and inhibits apoptosis in acute myeloid leukemia cell lines, including THP-1 [ 100 ].…”
Section: Discussionmentioning
confidence: 99%